ANALISIS KEMAMPUAN MAHASISWA DALAM MENULIS ARTIKEL JURNAL MELALUI LESSON STUDY DI UNIVERSITAS SIMALUNGUN - Huda, Muhammad Komarul; Zulfi, Ahmad; Damanik, Ali Akbar; Sari, Putri (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
The quality of learning can be improved, one of which is using lesson study, through collaboration between lecturers to achieve learning output, especially in scientific writing technique courses with journal article output, so that it has an impact on improving quality in higher education. This research uses lesson study through plan (planning), do (implementation), see (reflection) with the object of study in the technical course for writing scientific papers in 3 cycles, namely research-based scientific work, preparing an introduction to a journal article, compiling the results and discussion of a journal article. . The research sample consisted of 12 people, taking into account the students' ability to express opinions to achieve students' understanding in preparing journal articles until they were published in the target journal. The research results show that in each cycle there is an increase in expressing opinions and obtaining learning innovations in each cycle based on the results of reflection.